2022
DOI: 10.1101/2022.06.24.497468
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gene expression as phenotype - Many small-step changes leading to little long-term phenotypic evolution

Abstract: Unlike in genotypic evolution, there are few general rules governing phenotypic evolution with one of them being the small-step evolution. More specifically, natural selection tends to favor mutations of smaller phenotypic effects than of larger ones. This postulate can be viewed as a logical extension of Fisher's Geometric Model (FGM). Testing this FGM postulate, however, is challenging as the test would require a large number of phenotypes, each with a clear genetic basis. For such a test, we treat the expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…The changing evolvability of miRNA targets indicated that miRNA's regulation contribute to the evolution of organismal diversity ( Xu et al 2013 ). In a companion study on the evolution of gene expression under miRNAs ( Lin et al 2022 ) extends the connections in time scale from short-term development to long-term evolution, schematically represented as miRNA actions → GRN stability → developmental canalization → evolution. By showing the continual gains and losses of miRNA target sites during evolution, they suggest that miRNAs keep the target gene expressions near an optimal level, until the optimum shifts occasionally during long-term evolution.…”
Section: Discussionmentioning
confidence: 99%
“…The changing evolvability of miRNA targets indicated that miRNA's regulation contribute to the evolution of organismal diversity ( Xu et al 2013 ). In a companion study on the evolution of gene expression under miRNAs ( Lin et al 2022 ) extends the connections in time scale from short-term development to long-term evolution, schematically represented as miRNA actions → GRN stability → developmental canalization → evolution. By showing the continual gains and losses of miRNA target sites during evolution, they suggest that miRNAs keep the target gene expressions near an optimal level, until the optimum shifts occasionally during long-term evolution.…”
Section: Discussionmentioning
confidence: 99%